Professional Training of Would-be Teachers of English - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (ЗакДУ, 2013)
Резюме. У статті розглядаються методи модернізації професійної підготовки викладачів англійської мови. Виділено чотири основні групи навичок: конструктивні, організаційні, комунікативні й гностичні. Автор доходить висновку, що головною вимогою щодо вибору методів є організація навчального процесу як серії досліджень, у яких студент набуває знань і навичок самостійної роботи, цим самим посилюючи емоційне сприйняття для самовираження і творчої діяльності майбутніх викладачів англійської мови.

Abstract. In the industrial civilization language education was mainly a translator of knowledge and traditions of culture; in the informational civilization, however, it ought to become a mediator in acquiring knowledge, i.e. it should not only give ready knowledge, but also teach how to obtain, find and apply it in practice. To start training would-be teachers of English for a modern world we are to integrate up-to-date computer and communication technologies as well as practice into the syllabus on all the levels of professional training of teachers, especially in higher educational institutions.
Keywords: Professional Training; would-be teacher; English language